Pedagogical monitoring of the process of personal self-improvement of future preschool education teacher: the control stage - Шапаренко, Х. А. (Scientific notes of the pedagogical department, 2019)
The necessity of creating a system for monitoring the process of future pre-school education teachers` personal self-improvement during the educational process of the HEPE is shown. The issue of pedagogical monitoring of the process of future Preschool Education teachers` personal self-improvement as a specially organized observation of educational process by means of tracking by a certain method of pedagogical phenomena and values, which are selected for the control of parameters and their comparison with predetermined ones is exposed. The task of the final stage of monitoring is revealed, namely the definition of the state of teachers` personal self-improvement and determination of the formation degree of all personal self-improvement components (motivational, cognitive, axiological, procedural) according to certain criteria and indicators: ideological and cognitive (knowledge about structure, stages, components of personal self-improvement, ideological knowledge, professional knowledge), requirement and motivational (spiritual needs, motives for self-improvement, orientation of the personality), emotional and value (value orientations, conantivities, emotional intelligence), activity reflexive (the ability to personal self-design, the ability to personal self-realization, self-reflection).A comparison of the information obtained by means of pedagogical monitoring in the process of long and purposeful tracking of the progress and results of the educational process, personal self-improvement of future Preschool Education teachers with the help of used monitoring tools, analysis of the causes of increase or decrease in the value of indicators, revealing the dynamics of readiness levels of the future Preschool Education teacher to the personality self-improvement, prediction of keeping the persistent personality position throughout future teacher's life are made. The changes, which occurred at the level of personal self-improvement components formation of future Preschool Education teachers, are analyzed.